A Note On Assessment Of Soya Doc In Concentrate Diets Of Buffaloes - Dadhich, S.R.; Deshwal, A.K.; Paliwal , D.K.; Tailor , R.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Besides commonly used feed ingredients and protein sources, use of Bypass Protein Feed (BPF) is being recommended in dairy cattle feed as 65 % protein of it is rumen undegradable irrespective of its higher cost . Use of BPF is economical since per litre of milk allowances required is lower as compared to conventional balanced feed (Bhosale, 1998). For lactating cows solvent extracted soybean meal has a favourable amino acid profile (Schwab, 1995) and a high post ruminal protein digestibility (Stern et al., 1994). Soya DOC is utilized for extracting various types of peptides and essential amino acids. On the other end it is a good source of protein, hence present study was undertaken to evaluate its use as milk enhancer and its economics.